Louvre: A Framework for Metadata Curation in Data Ecosystem - Oliveira, Marcelo Iury S.; Lóscio, Bernadette Farias (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
Data Ecosystems are a cultural, technological, and social phenomenon based on the interplay of technology, actors and businesses, which provide an environment for creating, managing and sustaining data sharing initiatives. There is a general consensus as to the crucial role metadata can play on the Data Ecosystem. However, in most cases, the metadata management is underspecified, if not unaddressed at all. The employment of a metadata curation strategy can bring an ecosystem success and further ensure realization of Data Ecosystem actors’ purposes. In this work, our contribution is proposing a Metadata Curation Framework, called Louvre, which proposes a wide range of processes for curating metadata in Data Ecosystems. The promise is the employment of a well-conceived, efficient curation strategy for metadata.